Pengaruh Pertumbuhan Ekonomi Dan Disparitas Pendapatan Antardaerah Terhadap Kesejahteraan Masyarakat Provinsi Bali - Artana Yasa, I Komang Oka; Arka, Sudarsana (Jurnal Ekonomi Kuantitatif Terapan; 2015: Vol. 8, No. 1, Februari 2015 (pp. 1-112)DO - 10.24843/JEKT.2015.v08.i01.p07, 2015)
Public welfare is goal of development. Its can be seen from increasing economic growth and inequality in income distribution. Although welfare of Bali is increasing every year, but increase is still relatively low and still occurregionalincome disparities. This study aims to determine regional income disparitiesof Bali and the relationship between economic growth, regional income disparities ofpublic welfare. This study uses secondary data was analyzed using analysis of Index Williamson and path analysis. The analysis shows income disparity between regions of Bali Province in 2001-2012 decreased by an average value of 0.29 means that relatively low levels of disparity. Economic growth in a negative and significant impact on regional income disparities, but a positive and significant impact on public welfare. Regional income disparities in a negative and significant impact on public welfare. Economic growth was indirect effect on public welfare through regional income disparities. Local governments in development policy to pay attention to economic growth and income distribution in order to create a public welfare.
Keywords: economic growth, regional income disparities, public welfare